How intergenerational mobility shapes attitudes toward work and welfare - Schuck, Bettina; Shore, Jennifer (The annals of the American Academy of Political and Social Science, 2019)
Past experiences and expectations about the future shape how people think about work and welfare. Given the uncertainty many young people face when entering the labor market, we investigate whether 1) young peoples’ experiences of social mobility and 2) their future mobility expectations impact their attitudes regarding the meaning of work and welfare. Drawing on the concepts of self-interest and deservingness, we examine how both the experiences and expectations of intergenerational social mobility influence the ways in which young adults view the so-called moral dimension of work and welfare. Results of logistic regression analyses of around 11,000 young adults in eleven countries suggest that the relationship between mobility and individuals’ views on work and welfare varies depending on the dimension of mobility (economic and social origins, for example), with expected future mobility exerting a stronger effect on attitudes than past mobility experiences. We find that self-interest, not empathy with one’s social origins, appears to be the primary driver of these attitudes.
Gesehen am 06.05.2019